2019
DOI: 10.21037/jtd.2019.10.23
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy (CBT) for patients with chronic lung disease and psychological comorbidities undergoing pulmonary rehabilitation

Abstract: Background: The study aimed to determine the effects of adding cognitive behavioural therapy (CBT) to pulmonary rehabilitation to treat patients with chronic lung disease and comorbid anxiety and/or depression symptoms.Methods: An open, parallel group, randomised controlled trial (RCT) was conducted, with longitudinal follow-up of 12 months. CBT was delivered in 2 face-to-face sessions and 4 phone sessions to patients with depression or anxiety undergoing pulmonary rehabilitation. The main outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 67 publications
4
80
0
2
Order By: Relevance
“…The majority of studies were controlled trials (ie, CCT or RCT n= 24). [13][14][15][16][17][18][19][20][21][22][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In addition, there were six single group cohort designs, [49][50][51][52][53][54] two papers reported case exemplars 55,56 and one a phenomenological study. 57 Eight studies were not included as they reported the sub-analysis of a parent study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies were controlled trials (ie, CCT or RCT n= 24). [13][14][15][16][17][18][19][20][21][22][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In addition, there were six single group cohort designs, [49][50][51][52][53][54] two papers reported case exemplars 55,56 and one a phenomenological study. 57 Eight studies were not included as they reported the sub-analysis of a parent study.…”
Section: Resultsmentioning
confidence: 99%
“…[58][59][60][61][62][63][64][65] The majority of studies exclusively recruited people with COPD (78.7%, n=26). With the exception of Blumenthal et al 48 where 42% of participants had COPD, in the remaining seven studies, at least half the sample analyzed were categorized as COPD (Cully et al (75%), 41 Pumar et al (75%), 38 Cully et al (74%), 52 Cully et al (66%), 56 Jonker et al (51%), 45 Malpass et al (50%) 57 ). In studies reporting threshold criteria as an eligibility requirement (n=15, 45%), these ranged between including people with at least mild-to-moderate anxiety or depression (HADs-A ≥ 8, Beck Anxiety Inventory (BAI) scores 10-18, Beck Depression Inventory (BDI) ≥13) or clinically significant symptoms (State-Trait Anxiety Inventory STAI-STAIT ≥39, Patient Health Questionnaire PHQ-9 ≥10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…clinically stable settings [48], or with much different 6-minute walking distances. Further studies should clarify the effects of factors leading to a reduction in depression, including medical and psychotherapeutic interventions [56], as well as physical activity, exercise and rehabilitation [57][58][59][60], which may also influence test results and may in parallel improve the quality of life and possibly the outcome of COPD patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…The course of illness profoundly affects patient's physical, vocational and mental functioning, usually persistent, correlated with increased exacerbation rates, poor compliance and sometimes increased mortality thereby management of pulmonary conditions becomes even challenging. [10][11][12][13] Depression is not associated with survival in patients of interstitial lung disease, but is regarded as a major determinant of health related quality of life in patients with interstitial pulmonary fibrosis (IPF). 14,15 There may be both psychological and physical explanations to it, one hypothesis being; hypoxia renders brain damage that may lead to depression and suicide.…”
Section: Introductionmentioning
confidence: 99%